2017
DOI: 10.1007/s13534-017-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal polyp detection in endoscopic images using an improved feature extraction method

Abstract: Gastrointestinal polyps are treated as the precursors of cancer development. So, possibility of cancers can be reduced at a great extent by early detection and removal of polyps. The most used diagnostic modality for gastrointestinal polyps is video endoscopy. But, as an operator dependant procedure, several human factors can lead to miss detection of polyps. In this peper, an improved computer aided polyp detection method has been proposed. Proposed improved method can reduce polyp miss detection rate and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Polyp shows great differences throughout appearance in WE images [13]. This device uses a new texture to characterize WE images that integrate the benefits of transforming wavelets and a uniform local binary architecture [14]. As a classifier, comprehensive experiments on our current image information consisting of 700 standards WE images and 600 polyps images were chosen from 15 patients will verify that the proposed model for recognizing WE polyp images is promising [15], [16].…”
Section: Conventional Models and Their Importancementioning
confidence: 99%
“…Polyp shows great differences throughout appearance in WE images [13]. This device uses a new texture to characterize WE images that integrate the benefits of transforming wavelets and a uniform local binary architecture [14]. As a classifier, comprehensive experiments on our current image information consisting of 700 standards WE images and 600 polyps images were chosen from 15 patients will verify that the proposed model for recognizing WE polyp images is promising [15], [16].…”
Section: Conventional Models and Their Importancementioning
confidence: 99%
“…The comparisons exhibited the capabilities of different models in handling with clinical problems. Last, other reported data have shown that literature learning is another approach to determine the efficiency of developed models[ 106 , 181 ]. However, this type of comparative method is not reliable due to the inconsistency of research baselines, such as differences in datasets, hardware performance, and running time.…”
Section: Features Limitations and Future Perspectivesmentioning
confidence: 99%
“…Significant progress has been made in image recognition primarily due to the recent revival of deep learning, particularly the convolutional neural network (CNN), a class of artificial neural networks that have been widely used in biomedical and clinical research[1]. For example, the potential use of CNNs has been shown in the detection of gastrointestinal bleeding in wireless capsule endoscopy images using handcrafted and CNN features[2], diagnosis of Helicobacter pylori infection based on endoscopy images[3,4], and detection of gastrointestinal polyps using endoscopy images[5,6]. There is also a surge of interest in the potential of CNNs in radiology research[1,7] and in cellular and histopathological examinations[8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the ability of the CNN algorithms in (1) Lesion detection, a prevalent task for endoscopists, radiologists, and pathologists to detect abnormalities with medical images. These include the detection of colonic polyps, the detection of lesions on radiological images, and the detection of histopathological malignant changes on biopsy images[1,5-9]. CNN algorithms are also useful for (2) Classification, the CNNs utilise target lesions depicted in medical images, and these lesions are classified into classes.…”
Section: Introductionmentioning
confidence: 99%